Prevalence of equine leptospiral shedding using urine polymerase chain reaction and serum microscopic agglutination testing - Trimble, Amanda Carroll (Kansas State University, 2018)
Leptospirosis is a worldwide veterinary and public health concern, and emerging infectious disease of horses. The spirochete can be directly transmitted by contaminated urine, placental fluids, semen, infected tissues, reservoir hosts, or flood waters. Seroprevalence and infecting serovar vary with geography, yet diagnosis using the gold standard microscopic agglutination test (MAT) merely confirms a high exposure rate. Subclinical infection can complicate diagnosis. The aims of this study were to use semi-nested PCR on urine from apparently healthy horses to determine period prevalence of leptospiral shedding and to correlate these findings with MAT results to establish associations with client based survey data regarding horse management and environment. Serum and free-catch urine were collected from 204 healthy horses between May 2016- December 2017. Serum was used to determine GGT, creatinine concentrations, and six serovar MAT (Canicola, Hardjo, Icterhemorrhaegiae, Pomona, Grippotyphosa, Bratislava). Urine samples were submitted for PCR testing of leptospiral 23S rRNA. Client consent and survey data were collected for all subjects. Potential risk factors included drinking water source, exposure to livestock and dogs, geographical location, season, and precipitation. Two horses were positive on urine PCR for leptospirosis (shedding prevalence 1%), yet only one had a high reciprocal MAT titer of ≥800. Both horses were negative on urine PCR one month later without treatment. Approximately 77% of horses (157/204) were seroreactive (MAT reciprocal titer ≥100) for at least one serogroup, and Bratislava was detected more frequently than others (47.5%; (97/204)). Apparently healthy horses infrequently shed Leptospira spp. in urine, yet seroreactivity in clinically normal horses is high (77%), confirming high exposure rates to Leptospira spp. in the Central Midwest. Further studies should target serovar specific PCR tests and incorporate PCR testing in horses clinically affected with leptospirosis.
Prevalence of equine leptospiral shedding using urine polymerase chain reaction (PCR) and serum microagglutination testing (MAT)
Keywords: Equine; Leptospirosis